Application new chitosan derivatives as inhibitor corrosion on steel with coating method - Suyanto, Dr. Ir. M.Si. (2015)
Steel corrosionl could be inhibited with two new chitosan derivates, carboxymethyl chitosan-urea-glutaricacid (CMChi-UGLU) and carboxymethyl chitosan-benzadehyde(CMChi-B). The corrosion process in chloric acid and sodium chloride solution media could inhibit corrosion by coating method. The maximum of inhibition efficiency achieved by CMChi-B is 99.79 % in 2M HCl as media and for CMChi-UGLU the maximum of inhibition efficiency is 92.59 % in 2 % NaCl solution as media.